Accelerating understanding of resilient agriculture. Using a data sprint to catalyze new insights from existing evidence - Jones, Kristal; Nowak, Andreea C.; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Key messages